2012
DOI: 10.1136/bmjopen-2011-000754
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for forced or coerced sex among school-going youth: national cross-sectional studies in 10 southern African countries in 2003 and 2007

Abstract: ObjectivesTo study prevalence at two time points and risk factors for experience of forced or coerced sex among school-going youth in 10 southern African countries.DesignCross-sectional surveys, by facilitated self-administered questionnaire, of in-school youth in 2003 and 2007.SettingSchools serving representative communities in eight countries (Botswana, Lesotho, Malawi, Mozambique, Namibia, Swaziland, Zambia and Zimbabwe) in 2003 and with Tanzania and South Africa added in 2007.ParticipantsStudents aged 11–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 41 publications
(40 reference statements)
2
55
2
Order By: Relevance
“…An alternative explanation for acquisition among youth who did not report debut is sexual abuse. In South Africa, boys 15–26 frequently report perpetrating rape [31] and school-age boys and girls report being victims of forced or coerced sex [33], events that may not have been reported in questions about debut and partnerships.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation for acquisition among youth who did not report debut is sexual abuse. In South Africa, boys 15–26 frequently report perpetrating rape [31] and school-age boys and girls report being victims of forced or coerced sex [33], events that may not have been reported in questions about debut and partnerships.…”
Section: Discussionmentioning
confidence: 99%
“…Although few countries have conducted population-based surveys on child sexual abuse (CSA), the magnitude of the problem in Africa (Andersson et al, 2012; Lalor, 2004a,b; Moore, Awusabo-Asare, Madise, John-Langba, & Kumi-Kyereme, 2007; Pitche, 2005; World Health Organization –WHO, 2013) and the developed world (Gilbert et al, 2009) is alarming.…”
Section: Introductionmentioning
confidence: 99%
“…Sexual violence is on the rise: 31 % of women in Tanzania, 59 % in rural Ethiopia (WHO 2005);13-16 % in Kenya (WHO 2005;Adudans et al 2011), and 10 % of adolescents in South Africa have been sexually abused. A study in ten southern African states (Botswana, Lesotho, Malawi, Mozambique, Namibia, Swaziland, Zambia, Zimbabwe, Tanzania, and South Africa) revealed that 19.6 % (4,432/25,840) of female students and 21.1 % (4,080/21,613) of male students aged 11-16 years had experienced forced or coerced sex (Andersson et al 2012). The high prevalence of forced sex is part of the reason for the high incidence of HIV/AIDS in the region.…”
Section: Sexual Behaviourmentioning
confidence: 99%